The diminutive colon polyp: biopsy, snare, leave alone?. Issue 1 (January 2016) - Murino, Alberto; Hassan, Cesare; Repici, Alessandro
Abstract : Purpose of review: Diminutive polyps, measuring between 1 and 5 mm, represent the vast majority of colorectal polyps encountered during screening colonoscopy. Although the chance of harboring advanced adenoma or neoplastic cells is low, ensuring a complete polyp resection with clear margins is crucial to reduce the risk of interval colorectal cancer. The purpose of this review was to evaluate the different methods applied for polypectomy of diminutive polyps and clarify whether a diminutive polyp should be retrieved or left in place. Recent findings: Cold biopsy polypectomy is indicated for resection of polyps measuring 1–3 mm and removal of 4–5 mm polyps should be ensured by cold snare polypectomy. Over the last decade, hot biopsy polypectomy has been gradually abandoned because of an increased risk of diathermic injury. The resect and discard strategy and the diagnose and disregard strategy should be performed only by expert endoscopists, who should use validated scales and document the polyp features by storing several endoscopic images. Summary: Nowadays, complete resection of diminutive polyps, following the most appropriate technique, is recommended in clinical practice. The resect and discard strategy and the diagnose and disregard strategy should be reserved to expert endoscopists.